2019
DOI: 10.1371/journal.pone.0222275
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and perceptions towards hypoglycaemia in patients with diabetes mellitus: A multinational cross-sectional study

Abstract: BackgroundPreventing hypoglycaemia is an essential component of diabetes self-management that is affected by patients’ attitudes and perceptions. This study aimed to explore the hypoglycaemia problem-solving ability of patients who have diabetes mellitus and factors that determine their attitudes and perceptions towards their previous events.MethodologyA cross-sectional study was conducted between October 2017 and May 2018 in three Arab countries (Jordan, Saudi Arabia and Kuwait) in patients with diabetes mell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Patient-provider awareness of relevant ADRs associated with patients’ medications and adequate patient-provider communication were important aspects in the management of ADRs in less-controlled healthcare environment such as primary care [ 14 ]. However, only about one-third of patients in the community had received information on ADRs [ 109 , 110 ]. Healthcare professionals are often hesitant in giving information about important ADRs due to potential nocebo effects (i.e., perceived adverse effects as the result of negative expectancies) [ 111 ], nevertheless, a previous study showed the opposite, i.e, not receiving information on potential side effects from healthcare professional was associated with increased risk of self-reported ADRs and decreased satisfaction [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient-provider awareness of relevant ADRs associated with patients’ medications and adequate patient-provider communication were important aspects in the management of ADRs in less-controlled healthcare environment such as primary care [ 14 ]. However, only about one-third of patients in the community had received information on ADRs [ 109 , 110 ]. Healthcare professionals are often hesitant in giving information about important ADRs due to potential nocebo effects (i.e., perceived adverse effects as the result of negative expectancies) [ 111 ], nevertheless, a previous study showed the opposite, i.e, not receiving information on potential side effects from healthcare professional was associated with increased risk of self-reported ADRs and decreased satisfaction [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that patients who receive such information will better manage the drug reactions and become less worried [ 43 , 112 ]. In specific therapeutic areas such as diabetes management, previous studies found that up to 48% patients were often uninformed about drug-induced hypoglycemia risk and thus unable to recognise this reaction [ 109 , 110 , 113 ]. This highlights the need for better education strategies by their primary care providers as the majority of patients with chronic diseases were routinely managed in the primary care setting [ 114 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the practice level, antidiabetic therapy de-intensification, treatment protocols revisions, and enhancing patients' awareness of symptoms and prevention methods are needed. 41 Regular HbA1c…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, physicians should provide further education to their patients on how to self‐manage their hypoglycaemic events, as majority of these events are of mild to moderate severity and do not need hospitalisation. A previous study in Jordan highlighted that patients with diabetes mellitus have moderate problem‐solving ability towards their hypoglycaemic events, specifically, physicians need to emphasise in their education on the overall problem‐solving perception of hypoglycaemia and its immediate management 44 …”
Section: Discussionmentioning
confidence: 99%